27.2k views
3 votes
PLEASE HELP

1.In the solution of the equation 5 + 3x = -2x + 9, 2x is added to the equation first. Which of the following should be done next?

A.add -9
B.add -5
C.add -3x

User Marinbgd
by
5.9k points

1 Answer

7 votes

Answer:

B. add -5

Explanation:

5 + 3x = 9 - 2x

5 + 3x + (2x) = 9 - 2x + (2x)

5 + 5x = 9

The next step would be to subtract 5, to isolate the variable

5 + 5x + (-5) = 9 + (-5)

This would give you the x on one side, and coeficcient on the other

5x = 5

x = 1

User Barq
by
5.4k points